The efficiency dependance of a single-circuit power unit with a helium-cooled reactor and a hydrogen module on the degree of regeneration - Nurym, K.A.; Antonova, A.M.; Sakipov, K.E.; Vorobyev, A.V.; Stetsov, N.V. (Karagandy University of the name of acad. E.A. Buketov, 2025)
The most attractive single-circuit scheme of the power unit was chosen. Helium at the outlet of the reactor core enters the steam generator, where it gives part of the heat to generate highly superheated steam for the electrolysis plant. Next, helium operates in a closed gas turbine cycle with heat recovery. A gas-cooled reactor with a turbine and compressor allows the use of a thermodynamic cycle with high efficiency. A series of design calculations of the regenerator for various degrees of regeneration have been performed. A series of assessments of the effect on the real resistance of the regenerator from the high- and low-pressure sides have been carried out. The thermal scheme of energy production is calculated in accordance with a series of design calculations of the regenerator.
Keywords: reactor; helium; gas-turbine installation; regenerator; hydraulic resistance; aerodynamics resistance